Atypical squamous metaplasia in a benign cystic thyroid nodule mimicking high‐grade carcinoma. Issue 8 (5th December 2011) - Pellicer, Daniel L.; Sadow, Peter M.; Stephen, Antonia; Faquin, William C.; Michael, Claire W.
<x xml:space="preserve">Abstract</x> Squamous metaplasia (SM) occurs in a variety of thyroid conditions, both neoplastic and non‐neoplastic. In a small subset of benign thyroid lesions, SM can create a diagnostic pitfall by mimicking a malignant process. Here, we describe the case of a 52‐year‐old male with a 1.5 cm right thyroid nodule. Ultrasound‐guided fine‐needle aspiration biopsy showed markedly atypical, mitotically active epithelial cells which were suspicious for high‐grade carcinoma. Resection of the nodule demonstrated a follicular adenoma with cystic changes and atypical SM of the cyst‐lining component. As illustrated here, SM of the thyroid represents an important diagnostic pitfall for the cytopathologist, and should be included in the differential diagnosis of thyroid nodules, particularly those with potentially benign cystic changes. Diagn. Cytopathol. 2013;41:706–709. © 2013 Wiley Periodicals, Inc.